PEDOT-decorated nitrogen-doped graphene as the transparent composite film for the counter electrode of a dye-sensitized solar cell. (March 2015) - Chen, Pei-Yu; Li, Chun-Ting; Lee, Chuan-Pei; Vittal, R.; Ho, Kuo-Chuan
Abstract: A honeycomb-like composite film of nitrogen-doped graphene and poly(3, 4-ethylenedioxythiophene) (NGr/PEDOT) was prepared as a highly-efficient catalytic material for the counter electrode (CE) of a dye-sensitized solar cell (DSSC). The NGr was intended for increasing the conductivity and electrocatalytic ability of the composite film, and the PEDOT was used for a strong adhesion of the composite film to the substrate and for large surface area. The DSSC with the NGr/PEDOT composite CE exhibited a power conversion efficiency ( η ) of 8.30±0.03% for front-side illumination and 6.10±0.02% for back-side illumination. The DSSC with a Pt CE showed an η of 8.17±0.01% for front-side illumination and 5.76±0.05% for back-side illumination. The composite catalytic film of NGr/PEDOT is a low-cost alternative for replacing the conventional and expensive Pt film. Another DSSC was fabricated, in which its counter electrode contained a flexible Ti foil as the substrate and the NGr/PEDOT film as the catalytic film. This DSSC with its flexible CE exhibited an η of 8.53±0.02%. Graphical abstract: Highlights: Honeycomb NGr/PEDOT composite functions as the catalytic counter electrode (CE). Transparent NGr/PEDOT CE is used for bifacial dye-sensitized solar cells (DSSCs). The DSSC with NGr/PEDOT CE gives an η of 8.30±0.03% from front-side illumination. The same cell reaches an η of 6.10±0.02% from back-side illumination. The NGr/PEDOT on flexible Ti foil renders its DSSC the highest η of 8.53±0.02%.